Global development finance : (The World Bank, 2002)
This two volume set gives comprehensive coverage of global development finance for the year 2002. The first volume focuses on the effectiveness of international resource transfers, with a chapter each devoted to: recent trends and prospects for private capital flows; effectiveness of private capital flows in boosting investment and productivity; analysing progress in increasing the effectiveness of aid and the HIPC initiative; and financing international public goods. The second features the country tables.